Practical Model of Mobile Learning Applications - Fitro Nur Hakim (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
The mobile device has been supported by the operating system that makes the phone has the potential to be a learning tool. The Android operating system is the mobile platform of high potential in education, plus it is open source, it can support independent learning. Availability of facilities and applications that can be installed offline, allowing an independent learning process starts from the students themselves. The purpose of this research is to find a practical model that can be applied in learning. Make mobile learning a practical model that can be used teachers, students and schools take advantage of the resources that already exist. The research method uses research and development, to mobile learning models that later developed into a model factual. Results The study concluded that: Android mobile application that is filled with interesting teaching materials can continue to invite progress within teacher as creator and students as users. Availability of Internet applications, making new teaching participants, can catch up with learning by opening apps without worry about the royalty claims. Android mobile application that supports online messaging greatly help communication between members. Results of the study are: a practical mobile learning model consists of four aspects, namely: Four Key Roles, Learning Tasks Accommodation, Interactive Content and the Modular Learning Outcomes.